World in 2004 (The Economist Newspaper Ltd LondonGB, 2003)
Focuses on events that are anticipated to occur in 2004 in various parts of the world. Looks also at developments in business, finance and science and technology. Presents the world in figures.
Keywords: ECONOMIC CONDITIONS